REFLEXOS DO TECNOESTRESSE SOBRE O COMPORTAMENTO ORGANIZACIONAL - Ferreira, Aline Silva (2017)
Due to competitivity, companies adhered to Information and Communication Technologies (ICT) for increasing productivity and results. In this sense, technology improved quality and productivity in workers’ routine, but excessive use of ICT can lead to the technological stress known as technostress. Some aspects of creating technological stress relates to information overload and constant connectivity, denominated as techno-overload and techno-invasion. This study analyzed reflexes of the technostress in the organizational behavior. Using a quantitative approach, data was collected through a research instrument with 331 questionnaires answered. It concludes that techno-overload and techno-invasion influence positively work-family conflict, so excessive use of ITC can generate discomfort in the professional’s life. Results point that it was not possible to indicate influence of techno-overload and techno-invasion relating to affective organizational commitment and turnover intention. It verifies that there is low influence of the Techno-invasion relating to job satisfaction, and it was not possible to confirm influence on job satisfaction by techno-overload.